MANAJEMEN LABA : PERENCANAAN PAJAK, KUALITAS AUDIT DAN KEPEMILIKAN INSTITUSIONAL - Fitri, Baiq Fitri Arianti; Siarwi, Siarwi (ANALISIS, 2024)
The purpose of this study is to measure and analyze tax planning, audit quality and institutional ownership of earnings management. This research uses a sample of manufacturing companies listed on the Indonesia Stock Exchange in 2017 - 2021. The method for determining the sample for this research is a purposive sampling method using the Statistical Package for Social Science (SPSS) version 25.0 for data analysis. The type of research in this research is quantitative with descriptive methods, 17 companies were obtained as research samples with observations for 5 (five) years, so the total observation was 85 annual report data. The analysis technique used is multiple linear regression. The findings in this research are (1) Tax Planning has an effect on Profit Management, (2) Audit Quality has no effect on Profit Management, (3) Institutional Ownership has no effect on Profit Management, (4) Tax Planning, Audit Quality and Institutional Ownership have an effect significant to Earnings Management. The implication of this research is that it is hoped that the results of this research will not only contribute to manufacturing companies but also all companies listed on the IDX, so that they can increase insight and knowledge of tax avoidance so that management is able to design company mechanisms well and not carry out tax avoidance illegally and must be appropriate. with laws established by the government.